Community Participation in Organization Election of Local Head at the Time of the Covid-19 Pandemic in 2020 in Banten Province (Case Study: Serang Regency, Pandeglang Regency, Cilegon City and South Tangerang City) - Dairul Dairul; Bahrullah Akbar; Aries Djaenuri; Sampara Lukman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
In community participation, the implementation of regional head elections is the embodiment of the representative function inherent in the sovereignty of the people. The function of representation is one of the functions of government. For this reason, the selection represents the object of the form of Government Science. This study is to measure "Community Participation in the Implementation of Simultaneous Regional Head Elections During the Covid-19 Pandemic Period" in 2020 in Banten Province (Case Study: Serang Regency, Pandeglang Regency, Cilegon City and Tangerang City) community participation in the implementation of Pilkada. This study uses a qualitative research design with a descriptive type of research. The research informants were carried out by means of interviews, observations and literature studies as the techniques used in collecting data. Meanwhile, data reduction, data presentation and conclusion drawing are the technical data analysis in this research. The analysis used in this study is political participation from The International Encyclopedia of the Social Sciences, a conceptual definition is drawn up that Public Participation in Simultaneous Regional Head Elections is the active involvement of voters in various series of voter participation levels in the simultaneous Regional Head Elections (Pilkada) in 2020 in Banten Province more than 60 percent voter participation rate in four regencies/cities holding simultaneous regional elections on 9 December 2020. Pandeglang Regency in 2020 was 68.7 percent in 2015 56%., percent, Cilegon City in 2020 was 79.79 percent, in 2015 it was 63.51 percent exceeding the National target, Serang Regency in 2020 is 63.3 percent from the 2015 Pilkada only 50.8 percent, South Tangerang City in 2020 is 60.4 percent. In 2015, voter turnout was 57 percent, this shows a very significant increase even though we are currently being hit by the Covid 19 pandemic, which is extraordinary, it should be recorded in history. Simultaneously during the 2020 Covid-19 Pandemic Period in Banten Province.